Respuesta :

Answer:

Step-by-step explanation:

Factoring  x2-6x-30

The first term is,  x2  its coefficient is  1 .

The middle term is,  -6x  its coefficient is  -6 .

The last term, "the constant", is  -30

Step-1 : Multiply the coefficient of the first term by the constant   1 • -30 = -30

Step-2 : Find two factors of  -30  whose sum equals the coefficient of the middle term, which is   -6 .

     -30    +    1    =    -29

     -15    +    2    =    -13

     -10    +    3    =    -7

     -6    +    5    =    -1

     -5    +    6    =    1

     -3    +    10    =    7

     -2    +    15    =    13

     -1    +    30    =    29

The correct answer is 29 vertex
ACCESS MORE